Exploring Financial Fraud in Indonesian Manufacturing: 2016-2019 Analysis: Analisis Keuangan dan Kecurangan: Manufaktur Indonesia 2016-2019. - Noviana Dewi; Wiwit Hariyanto (Universitas Muhammadiyah Sidoarjo, 2024)
This study aims to determine the effect of Financial Stability, External Pressure, Personal Financial Need, Financial Targets on Financial Statement Fraud with a Fraud Triangle Perspective in Manufacturing Companies Listed on the Indonesia Stock Exchange in 2016-2019. The sampling method used is purposive sampling method. The number of companies sampled in this study were 13 Food and Beverage Companies Listed on the IDX for the 2016-2019 Period. The data used is secondary data. The data analysis method used in this research is Multiple Linear Regression. The results of this study indicate that Financial Stability affects Financial Statement Fraud with a Fraud Triangle Perspective on Food and Beverage Companies listed on the Indonesia Stock Exchange (IDX) in the 2016-2019 period. External Pressure affects Financial Statement Fraud with a Fraud Triangle Perspective on Food and Beverage Companies listed on the Indonesia Stock Exchange (IDX) in the 2016-2019 period. Personal Financial Need affects Financial Statement Fraud with a Fraud Triangle Perspective on Food and Beverage Companies listed on the Indonesia Stock Exchange (IDX) in the 2016-2019 period. Highlights: Fraud Triangle Perspective: The study adopts a Fraud Triangle perspective, emphasizing the interplay of Financial Stability, External Pressure, and Personal Financial Need in contributing to Financial Statement Fraud among Food and Beverage Companies on the Indonesia Stock Exchange. Sample Precision: With a purposive sampling method, the study meticulously selects 13 Food and Beverage Companies listed on the IDX for the 2016-2019 period, ensuring a focused examination of the chosen entities. Key Findings: The research reveals significant associations, indicating that Financial Stability, External Pressure, and Personal Financial Need all play substantial roles in influencing Financial Statement Fraud within the specified timeframe for the selected companies on the Indonesia Stock Exchange. Keywords: Financial Stability, External Pressure, Personal Financial Needs, Financial Targets , Fraud Financial Statements, Fraud Triangle